Icônes de l'art moderne la collection Chtchoukine : catalogue de l'exposition : Fondation Louis Vuitton, 22 octobre 2016-20 février 2017 - Baldassari, Anne 1955- (Gallimard, 2016)
The Fondation Louis Vuitton's unprecedented exhibition brings together one hundred and thirty masterpieces, among the most iconic of the collection created in Moscow by the great Russian art patron, Sergei Shchukin. From Le Déjeuner sur l'herbe (1866) by Claude Monet, the hieratic Mardi gras (1888-90) by Paul Cézanne, Paul Gauguin's Tahitian odalisque Eh quoi, tu es jalouse? (1892), the luminescent panel L'Atelier du peintre (1911) by Henri Matisse, to conclude with Pablo Picasso's Trois femmes (1908) and the collage Compotier, grappe de raisin, poire coupée (1914), the magnificence of Shchukin's collection is most fittingly exhibited here. Extended by a group of sorne thirty major works from the Russian avant-gardes, including Counter Relief (1916) by Vladimir Tatlin, Green Stripe (1917) by Olga Rozanova, and Kazimir Malevich's monochrome painting, Black Suprematie Square (1929), Icons of Modern Art covers the extreme breadth of this journey through nineteenth- and twentieth-century creation. The presentation of these exceptional works, where our collective gaze cornes together, constitutes an exemplary "painting lesson."